Honeybee Cognition as a Tool for Scientific Engagement - Jai A. Denton; Ivan Koludarov; Michele Thompson; Jarosław Bryk; Mariana Velasque (Insects, 2021)
Apis mellifera (honeybees) are a well-established model for the study of learning and cognition. A robust conditioning protocol, the olfactory conditioning of the proboscis extension response (PER), provides a powerful but straightforward method to examine the impact of varying stimuli on learning performance. Herein, we provide a protocol that leverages PER for classroom-based community or student engagement. Specifically, we detail how a class of high school students, as part of the Ryukyu Girls Outreach Program, examined the effects of caffeine and dopamine on learning performance in honeybees. Using a modified version of the PER conditioning protocol, they demonstrated that caffeine, but not dopamine, significantly reduced the number of trials required for a successful conditioning response. In addition to providing an engaging and educational scientific activity, it could be employed, with careful oversight, to garner considerable reliable data examining the effects of varying stimuli on honeybee learning.